2010
DOI: 10.1103/physrevd.82.014010
|View full text |Cite
|
Sign up to set email alerts
|

New interpretation for theDs2*(2573)and the prediction of novel exotic charmed mesons

Abstract: In this manuscript we study the vector-vector interaction within the hidden-gauge formalism in a coupled channel unitary approach. In the sector C ¼ 1, S ¼ 1, J ¼ 2 we get a pole in the T matrix around 2572 MeV that we identify with the D Ã s2 ð2573Þ, coupling strongly to the D Ã K Ã ðD Ã s ð!ÞÞ channels. In addition we obtain resonances in other exotic sectors which have not been studied before such as C ¼ 1, S ¼ À1, C ¼ 2, S ¼ 0 and C ¼ 2, S ¼ 1. These ''flavor-exotic'' states are interpreted as D Ã " K Ã , … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
127
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 49 publications
7
127
1
Order By: Relevance
“…Similarly, consistency with experiment has been shown in J/ψ → φ(ω)R [14], with R any of the resonances of [11], and in J/ψ radiative decays in [15]. The extension of these ideas to the charm and hidden charm sector have also shown that some of the excited D states and X,Y,Z states recently reported could be explained in terms of molecules involving mesons with charm [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 64%
“…Similarly, consistency with experiment has been shown in J/ψ → φ(ω)R [14], with R any of the resonances of [11], and in J/ψ radiative decays in [15]. The extension of these ideas to the charm and hidden charm sector have also shown that some of the excited D states and X,Y,Z states recently reported could be explained in terms of molecules involving mesons with charm [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 64%
“…We refer to 8 for a detailled explanation. The hidden-gauge formalism is applied in order to describe the interaction between vector mesons and vector mesons with pseudoscalars and photons 3 .…”
Section: Formalismmentioning
confidence: 99%
“…The molecular picture can also be applied to further states, though the vector-vector interaction does not always provide sufficient attraction. Only those carrying the quantum number hidden charm (C = 0; S = 0), (C = 1; S = −1, 0, 1) and (C = 2; S = 0, 1), form molecules of two D * mesons or D * and ρ, K * [22,23]. Some of these cases are flavour exotics since they can not be reached by qq [23].…”
Section: Introductionmentioning
confidence: 99%
“…Only those carrying the quantum number hidden charm (C = 0; S = 0), (C = 1; S = −1, 0, 1) and (C = 2; S = 0, 1), form molecules of two D * mesons or D * and ρ, K * [22,23]. Some of these cases are flavour exotics since they can not be reached by qq [23]. Of particular interest is the doubly charmed states of C = 2, which is a challenge also for experiments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation